Insomnia : [large type] a novel - Pinborough, Sarah, 1972- (Harper Large Print, an imprint of HarperCollinsPublishers, 2022)
In this twisty, mind-bending thriller from the bestselling author of Behind Her Eyes, Emma Averill worries that her crippling insomnia is a sign that she's slowly going insane-like the mother she's worked so hard to leave in her past--